Critical Limit of Zinc for Rice in Calcareous Soils - Rahman, MA; Jahiruddin, M; Islam, MR (Journal of Agriculture & Rural Development, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> A pot culture experiment was conducted to determine the critical limit of Zn for rice grown in calcareous soils collected from the High Ganges River Floodplain (AEZ 11). The soils contained CaCO3 0.68-6.95%, pH 7.1-7.8, organic matter 1.32-2.49% and clay 9.0-33.0%. The available Zn content of soils was estimated by three extraction methods and the amount of extraction followed the order of 0.1M HCl > 0.005 M DTPA (pH 7.3) >1M NH4OAc (pH 7.0). The critical levels of DTPA, HCl and NH4OAc extractable Zn were found to be 0.83, 1.80 and 0.40 ppm, respectively for rice as determined by Cate and Nelson's graphical procedure. The DTPA extractable Zn showed a positive correlation with DM yield and plant Zn content. Thus, the DTPA extraction can be regarded as a good method for determining available Zn status in calcareous soils. Key words: Calcareous soil, critical limit, rice, zinc. DOI = 10.3329/jard.v5i1.1456 J Agric Rural Dev 5(1&2), 43-47, June 2007